Associations between bullous pemphigoid and primary malignant cancers: An English national record linkage study, 1999-2011 - Ong, E; Goldacre, R; Hoang, U; Sinclair, R; Goldacre, M (2014)
We conducted a nationwide record-linked study using all English NHS hospital admission data and mortality statistics from 1999 to 2011 to evaluate the risk of concurrent or subsequent bullous pemphigoid (BP) in a cohort of 2,873,720 individuals with malignant cancers, when compared with a reference cohort. We calculated standardised rate ratios (RRs) based on person-years at risk, comparing the observed and expected numbers of BP cases in the cancer cohort with those in the reference cohort. Overall, the cohort of people with a record of a malignant cancer was not found to be at greater risk of concurrent or subsequent BP than the cohort of people without a record of a malignant cancer (RR 0.96, 95 % CI 0.88-1.04), although elevated risks of BP were found in sub-cohorts of people with either kidney cancer, laryngeal cancer or lymphoid leukaemia. We also similarly analysed the risk of concurrent and subsequent malignant cancers in a cohort of people with a principal diagnosis of BP, and again found no increased risk as compared with the reference cohort (RR 1.00, 95 % CI 0.92-1.09). © 2013 Springer-Verlag Berlin Heidelberg.